Primary breast angiosarcoma in postmenopausal women with a picture like Kasabach-Merritt syndrome – A case report - Ćuk, Mirjana; Gajanin, Radoslav; Marić, Radmil; Marić, Veljko; Todorović, Svjetlana; Vasić Milanović, Milena (Vojnosanitetski pregled, 2021)
Introduction. Primary angiosarcoma of the breast (PAB) is a very rare tumor and accounts for 0.04% of all breast malignant tumors and most commonly occurs in young women. Kasabach-Merritt syndrome (KMS) is described as consumption coagulopathy with thrombocytopenia, and without adequate therapy almost certainly leads to a very fast lethal outcome. The literature contains only a few cases of PAB associated with thrombocytopenia or with KMS and there are no clear defined protocols for the treatment of these patients, which requires the presentation of as many cases as possible. Case report. We presented a rare case of 60-year-old postmenopausal woman with metastatic PAB grade III associated with a picture like KMS (thrombocytopenia and anemia without the coagulation factor disorder with massive bleeding in the tumor). Mastectomy was performed without the extirpation of the axillary region. After the surgery, improvement with anemia and thrombocytopenia was noticed. One month after the surgery, supportive and symptomatic therapy was administered, as well as bishosphonate therapy, but with temporary improvement. Deplasmated erythrocytes and methylprednisolone were added during the another hospital stay, but prominent symptoms of general weakness along with the progression od thrombocytopenia were noted. Fibrinogen and coagulation factors were within reference values all the time. The patient died four months after the surgery. Conclusion. PAB in postmenopausal women is a very rare tumor, and may be associated with anemia and thrombocytopenia without other laboratory parameters for KMS. Anemia and thrombocytopenia are refractory to standard treatment protocols, and also significantly reduces the quality of life of these patients.
Keywords: angiosarcoma of the breast; breast neoplasms; diagnosis; histological techniques; immunohistochemistry; kasabach-merritt syndrome; postmenopause; thrombocytopenia; treatment outcome